The Effects of Fly Ash and Cow Manure on Water Spinach Grown on An Ultisol of Lampung, Indonesia - Priyadi Priyadi; Rianida Taisa; Nurleni Kurniawati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Fly ash is the residue of coal combustion that can potentially be an ameliorant. Unfortunately, its use is limited by government regulations that are classified as hazardous and toxic materials. This study examines the effectiveness of fly ash and cow manure as an ameliorant for Ultisols. The experiment was carried out by two factors, i.e., the dose of fly ash, namely 0, 50, 100, and 150 t/ha, and the quantity of cow manure, i.e., 10, 20, and 30 t/ha. The results show that fly ash and cow manure could be ameliorants for low-pH soils such as Ultisols. The suitable dose of fly ash and cow manure as ameliorants in this study are 50 t/ha and 20 t/ha, respectively. Increasing the amount of fly ash caused a decrease in the growth of water spinach, plant height, number of leaves, fresh plant weight, root length, and dry weight of the root. In addition, fly ash increased pH 6.66-7.30, total P 31.74-52.21 mg/100 g, and total K 16.19-25.75 mg/100 g.